Effects of Xylazine and Dexmedetomidine on clinico-physiological and haemato-biochemical parameters during total intravenous anaesthesia in horses - K, RAJESH KUMAR; VADALIA, J V; BHATT, R H; BHADANIYA, A R; DODIYA, V D; PADALIYA, N R; ZALAVADIYA, S H (The Indian Journal of Animal Sciences, 2024)
The present study evaluated the clinico-physiological and haemato-biochemical parameters in 12 native breed horses, irrespective of age and sex, using two different total intravenous anaesthesia (TIVA) triple drip combinations, viz. xylazine, ketamine and guaifenesin (XKG group); and dexmedetomidine, ketamine, and guaifenesin (DKG group). Sedation in both groups was achieved with acepromazine and butorphanol, with xylazine used in the XKG group and dexmedetomidine in the DKG group, followed by ketamine induction and maintenance with the respective TIVA protocols. During different time intervals in the pre, peri and post-operative periods, both groups were assessed for clinico-physiological, haematological and biochemical parameters. The results showed that horses in the DKG group showed balanced and better cardiopulmonary and haemato-biochemical changes when compared to XKG group.